The Analysis of Association between Mindfulness, Religiosity, and Psychological Well-Being among Female University Students - Salbia Abbas, Rabia Hanif, Iqra Batool, Maria Ashraf, Taiba Afzal, Asma Rafiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Psychological well-being is an essential feature of mental health. An individual’s mental health is significant as physical health. Current research is determined to explore the association between mindfulness, religiosity and psychological well-being. Methods: A sample comprised of 100 female university students was obtained through convenient sampling. A self-developed demographic sheet was administered along with 42 item Ryff psychological well-being (PWB) Scale, Mindful Attention Awareness scale (MAAS) based on 15 item, and Muslim Religiosity Personality Inventory (MRPI). For data analysis, descriptive statistics, Pearson Product Moment Correlation Coefficient were applied. Results: Outcomes of study reveals moderate level of significant relationship between mindfulness and psychological well-being (r = 0.437) and very small correlation between (r = 0.18) religiosity and psychological wellbeing. The correlation is significant at the 0.01 level. Furthermore, the finding indicates that mindfulness will be effective for improving psychological well-being. Conclusion: In sum, it is concluded that people with high level of mindfulness have improved psychological well-being. Keywords: Mindfulness, religiosity, psychological well-being, mental health.